Official sites of central libraries of the Russian Federation constituent entities as a system-forming platform of information presentation on indigenous ethnic groups - N. I. Gendina; N. I. Kolkova (Библиосфера, 2016)
The paper considers the problem of preserving the civilization cultural diversity by creating online resources about indigenous peoples. Study results carried on by the Research Institute of Information Technologies in Social Sphere of Kemerovo State Institute of Culture are analysed. The research objective is to identify and analyze websites content including information about indigenous peoples. The investigation was based on the system of structural-functional and culturological approaches. The study established that owners of websites containing information on aboriginal peoples are the organizations engaged in the media, educational and research institutions, associations, cultural institutions, as well as individuals. The local index of the Internet resources owners about indigenous peoples is proposed that allows organizing and systematizing them into groups. The paper applies the analysis of information about indigenous peoples of Russia as a part of websites content of Central Libraries (CL) of the Russian Federation subjects. Materials on aboriginals at CL websites of the Russian Federation are fragmented, incomplete, implicit ways of information presenting. It is proved the necessity to create navigators of Internet resources devoted aboriginal peoples based on CL of the Russian Federation entities. It gives the possibility of dispersed material cumulative reflection in the Internet about them. The inclusion of electronic guides on the Internet resources about indigenous peoples into the local history block of official website of CL of Russian Federation subjects is aimed to solve the problem of high quality information-library service, the growth of the libraries social status in modern society.